2014
DOI: 10.1074/jbc.m114.596411
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-proliferative Function of the TGF-β1 Signaling Pathway Involves the Repression of the Oncogenic TBX2 by Its Homologue TBX3

Abstract: Background:The transcription factor TBX3 regulates the anti-proliferative function of the TGF-␤1 pathway but its downstream target(s) responsible for this is unknown. Results: TBX3 downstream of TGF-␤1 signaling represses TBX2 to inhibit proliferation. Conclusion:The down-regulation of TBX2 is required for the anti-proliferative function of the TGF-␤1-TBX3 axis. Significance: This study sheds light on the mechanisms involved in the anti-proliferative role of TGF-␤1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
(26 reference statements)
2
43
0
1
Order By: Relevance
“…and TBX3 are up-regulated in several cancers, and recent evidence suggests that whereas TBX2 functions as a pro-proliferative factor, TBX3 inhibits cell proliferation but promotes cancer cell migration and invasion. 65 Here, we detected downregulation of TBX2, belonging to the same T-box gene family, which product found to participate in the proliferation control. 65 Plasminogen activator urokinase (PLAU)…”
Section: Discussionmentioning
confidence: 74%
“…and TBX3 are up-regulated in several cancers, and recent evidence suggests that whereas TBX2 functions as a pro-proliferative factor, TBX3 inhibits cell proliferation but promotes cancer cell migration and invasion. 65 Here, we detected downregulation of TBX2, belonging to the same T-box gene family, which product found to participate in the proliferation control. 65 Plasminogen activator urokinase (PLAU)…”
Section: Discussionmentioning
confidence: 74%
“…The authors also revealed that TBX3 mediated the anti-proliferative and pro-migratory effects of TGF-β1 in these cells. In a follow-up paper they demonstrated that this anti-proliferative function involves the ability of TBX3 to directly bind and repress the pro-proliferative factor TBX2 (60). Finally, they showed that the TGF-β1/TBX3/TBX2 axis resulted in the upregulation of p21WAF1, leading to cell cycle inhibition.…”
Section: Transforming Growth Factor-beta 1 (Tgf-β1) Signalling Pathwaymentioning
confidence: 98%
“…Furthermore, ectopic overexpression of TBX3 in non-invasive WM1650 radial growth phase (RGP) melanoma cells and the upregulation of TBX3 by RA in vertical growth phase (VGP) melanoma cells reduced the proliferative capacity of the cells with the former being associated with an increase in migratory ability (58,59). It is important to note that Transforming growth factorbeta (TGF-β) contributes to breast cancer progression by inhibiting cell proliferation and promoting migration and recent studies have shown that TBX3 is required for the anti-proliferative and pro-migratory effects of TGF-β in breast epithelial cells (60,61). The mechanism(s) that determines whether TBX3 functions as a proproliferative or anti-proliferative factor is not known.…”
Section: Tbx3 In Senescence Apoptosis and Proliferationmentioning
confidence: 99%
“…Recently, Tbx3 was reported to serve a key role in melanoma migration and invasion by acting as a key substrate of protein kinase B and thus inducing the repression of E-cadherin (8). Additionally, Tbx3 is involved in the anti-proliferative event mediated by the transforming growth factor β1 signaling pathway by repressing the oncogenic Tbx2 in human breast epithelial MCF-12A cells (11).…”
Section: Introductionmentioning
confidence: 99%